2016
DOI: 10.1021/acs.jpcc.6b10088
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Stimulated Luminescence and First-Principle Study of Defect Configurations in the Perovskite-Type Hydrides LiMH3:Eu2+ (M = Sr, Ba) and the Corresponding Deuterides

Abstract: Temperature-dependent photoluminescence (PL) as well as thermoluminescence (TL) were studied in the Eu2+-doped hydrides LiMH3 (M = Sr, Ba) and the corresponding deuterides. Here, thermally stimulated luminescence was observed for the first time in a Eu2+-doped hydrides and deuterides. The onset temperature of quenching (T 95 %) and the quenching temperature (T 50 %) were determined from photoluminescence intensities, and the energy barrier for thermal quenching was estimated. Then, a scheme with the localizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…To go in deeper understanding, knowledge of the energy formation of defects, defects stability and defects energy position are required, through band structure and defects calculations. 83 Several spectroscopic techniques have been used to study the persistent luminescence mechanism such as: optical, Electron Paramagnetic Resonance (EPR) to control the origin and defects intensity, 84 X-rays spectroscopies to give insight to the mechanism , 85 thermoluminescence and photoconductivity 86,87 to measure the traps depth. 88 In the case of electrons traps and holes traps, 89 the stored charges can be released by various processes, as presented in the following part of this review, such as thermal, 90 optical 91 or others physical stimulations, 92 resulting in stimulated emissions from the active recombination centers.…”
Section: Traps and Co-dopingmentioning
confidence: 99%
“…To go in deeper understanding, knowledge of the energy formation of defects, defects stability and defects energy position are required, through band structure and defects calculations. 83 Several spectroscopic techniques have been used to study the persistent luminescence mechanism such as: optical, Electron Paramagnetic Resonance (EPR) to control the origin and defects intensity, 84 X-rays spectroscopies to give insight to the mechanism , 85 thermoluminescence and photoconductivity 86,87 to measure the traps depth. 88 In the case of electrons traps and holes traps, 89 the stored charges can be released by various processes, as presented in the following part of this review, such as thermal, 90 optical 91 or others physical stimulations, 92 resulting in stimulated emissions from the active recombination centers.…”
Section: Traps and Co-dopingmentioning
confidence: 99%
“…An increase of n from 1.6 to 2 is thus expected to more than double the radiative decay rate, which is in agreement with the observed decay rates in hydrides. Additionally, the Eu 2+ ‐doped inverse perovskites Li M H(D) 3 ( M = Sr, Ba) were also studied using thermally stimulated luminescence and shallow, intense glow peaks were observed . The results were compared to density functional calculations and models for different defect configurations in order to study qualitative trends for the stabilities of different possible defects.…”
Section: Eu2+‐doped Hydridesmentioning
confidence: 99%
“…For the past decades, hydrides and mixed anion hydrides containing Eu 2+ dopant have been reported to exhibit green-red luminescence. 10,[14][15][16][17][18][19][20] However, their poor stability in air and moisture limits their application. In contrast, we have recently demonstrated that oxyhydride GdHO is stable in ambient air and can act as a phosphor host for Tb 3+ .…”
Section: Introductionmentioning
confidence: 99%